Kondisi Keuangan Memoderasi Pengaruh Kesadaran Wajib Pajak, Pemahaman Perpajakan dan Kepatuhan Wajib Pajak Selama Pandemi Covid-19 - Febriyanthi, Ni Ketut Ayu; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi, 2023)
Taxpayer compliance is a scientific discipline run by taxpayers in order to carry out their obligations in the field of taxation according to applicable regulations. The aim of the research is to obtain information regarding the effect of taxpayer awareness and understanding of taxation on individual taxpayer compliance during the Covid-19 pandemic which is moderated by financial conditions. The number of samples taken using the slovin formula is 100 samples with simple random sampling technique. Questionnaires are used as data. Moderate regression analysis and multiple linear regression were used as data analysis techniques. In accordance with the results of data analysis, it was found that taxpayer awareness and understanding of taxation had a significant positive effect on individual taxpayer compliance during the Covid-19 pandemic. Financial conditions strengthen the influence of taxpayer awareness and understanding of taxation on individual taxpayer compliance during the Covid-19 pandemic. Keywords: Taxpayer Compliance; Taxpayer Awareness; Tax Understanding; Financial Condition